Żywność ekologiczna jako czynnik poprawy zdrowia - Szołtysek, Katarzyna; Dziuba, Szymon (The Use of Organic Food as a Factor of Health Improvement, 2008)
The following thesis presents a strict relation between health and nutritional behaviour. It has been proven that in an attempt to stay healthy more and more people, including Poles, choose organic food. The main reason for purchasing food from ecological farms is, above all, an attempt to avoid the health risk related with the consumption of conventional food. Organic food guarantees high nutritional value owing to the environmental conditions of production of agricultural products, along with the method of production, different from that of typical food. All these factors are enough to guarantee organic food quality. The functional properties of organic products contribute to human health, playing an essential preventory part in the human nutrition. The above-mentioned properties are a result of containing a vast range of ingredients. Ingredients such as vitamins (particular vit. C), mineral ingredients, essential fatty acid and also a more advantageous amino acid structure of protein, can be found much more frequently in ecological food than in conventional food. This conclusion was drawn not only on the basis of specialized literature but also on the basis of own research on aronia fruit from ecological agriculture. Thus, it can be stated with all certainty that ecological food constitutes a crucial element in health prevention. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 30, s. 95-103